Upaya Pencegahan Demensia pada Lansia Melalui Intervensi Edukasi dalam Bentuk Seminar Interaktif - Novian Budi Santoso; Hanna Tabita Hasianna Silitonga; Ronald Torang Marsahala Panggabean; Hebert Adrianto; Cindy Clara Sari; Najmul Laila; Nurul Illahi Muhammad Risha; Etha Rambung; Elizabeth Sulastri Nugraheni; Ni Njoman Juliasih (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Physical and mental changes in the elderly can have an impact on the health of the elderly. Dementia is one of the main health problems experienced by the elderly, characterized by decreased cognitive function that impacts quality of life and independence. Lack of public understanding of early detection, treatment, and prevention of dementia increases the risk of delayed treatment and worsens the condition of the elderly. This community service aims to increase knowledge and awareness of dementia through interactive seminars for the elderly and their families at GKI Sepanjang Sidoarjo. The results of the interactive seminar showed that the percentage of correct answers in the post-test increased by 13.14% from the pre-test. As many as five out of 10 questions with correct answers amounted to more than 50% of the total respondents. Judging from the answers obtained, program participants were not familiar with examples of cognitive functions and the definition of Hoarding Syndrome. At the end of this activity, there was an increase in participants' understanding of improving the health of the elderly, but there were still questions that participants could not answer. In conclusion, this activity succeeded in increasing health literacy related to dementia among the elderly and their families at GKI Sepanjang Sidoarjo, but other educational methods or media are needed to further increase the knowledge of the elderly regarding dementia.